Old age, commonly viewed as “inability, regress, fadedness”, appears as a leitmotiv in sylva’s33 triptych and Tadeusz Konwicki’s auto comments - Ossowska, Katarzyna (Starość i młodość w literaturze i kulturze, 2016)
Whole Tadeusz Konwicki’s works have been strongly influenced by his own personal experiences.In his work Kalendarz i klepsydra one can find the same motives, situations, figures and descriptions ofnature. However, one of the most repetitive leitmotive’s in his prose is ageing. In a very surprising waybecause of the fact that at the same time it is unpredictable and ironic, the author presents this topic in hisautobiographical prose — that is in sylva’s triptych consisted of Kalendarz i klepsydra, Wschody i zachodyksiężyca and Nowy Świat i okolice. It is quite an extraordinary situation taking into consideration the factthat during the publication of the first sylva Konwicki is fifty years old — is it the age when human startsthinking about death. That question will probably be left with no answer.It is highly likely that such way of thinking about death and ageing appeared in his works becauseof the intensity of the experience he had gained before throughout his half of a century life. Maybe it issome kind of trick to achieve the advantage over the dialogue between an intelligent reader and himselfas an author.Ageing in Konwicki’s works is multidimensional — it does not refer only to the physical ageing butalso to the process of literary creation. Therefore the main purpose of this article is to collect, describe andcategorise the most important topics and motives when Konwicki pretended to be old man.